2012
DOI: 10.1139/y11-094
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro characterization of the pharmacological effects induced by (–)-α-bisabolol in rat smooth muscle preparations

Abstract: The present study deals with the pharmacological effects of the sesquiterpene alcohol (-)-α-bisabolol on various smooth-muscle preparations from rats. Under resting tonus, (-)-α-bisabolol (30-300 µmol/L) relaxed duodenal strips, whereas it showed biphasic effects in other preparations, contracting endothelium-intact aortic rings and urinary bladder strips, and relaxing these tissues at higher concentrations (600-1000 µmol/L). In preparations precontracted either electromechanically (by 60 mmol/L K(+)) or pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…We demonstrated that α-bis can modulate LPS-induced hyperresponsiveness in an ARDS model by improving the lung function triggered by pretreatment with α-bis-LNCs, as observed by the decrease in lung elastance after a methacholine challenge. Consistent with our results, Siqueira et al 46 have shown that tracheal rings of rats challenged with ovalbumin and treated previously with α-bis (aerosol) reduced the hyperresponsive phenotype, and they showed that α-bis may act as an inhibitor of voltagedependent Ca 2+ channels. Similarly, Roberts et al, 47 using a porcine isolated tissue bath (from coronary and splenic arteries), demonstrated that α-bis was able to inhibit calciuminduced contractions and that the removal of extracellular calcium inhibited its responses.…”
supporting
confidence: 93%
“…We demonstrated that α-bis can modulate LPS-induced hyperresponsiveness in an ARDS model by improving the lung function triggered by pretreatment with α-bis-LNCs, as observed by the decrease in lung elastance after a methacholine challenge. Consistent with our results, Siqueira et al 46 have shown that tracheal rings of rats challenged with ovalbumin and treated previously with α-bis (aerosol) reduced the hyperresponsive phenotype, and they showed that α-bis may act as an inhibitor of voltagedependent Ca 2+ channels. Similarly, Roberts et al, 47 using a porcine isolated tissue bath (from coronary and splenic arteries), demonstrated that α-bis was able to inhibit calciuminduced contractions and that the removal of extracellular calcium inhibited its responses.…”
supporting
confidence: 93%
“…In fact, in the latter preparations, both EOOM and its main constituent E‐MC more potently inhibited cholinergic‐induced contractions than KCl‐induced contractions . This suggests that E‐MC acts against contractile responses that preferentially recruit pharmacomechanical coupling in rat airway tissues, a finding that is clearly different from other essential oils and volatile compounds that preferentially act on electromechanically induced contractions …”
Section: Discussionmentioning
confidence: 90%
“…) inhibited cholinergic‐induced contractions more potently than contractions elicited by KCl, with IC 50 values for the relaxant effects against carbachol‐induced contractions being significantly lower than those against KCl‐induced contractions . This suggests that, in rat airway tissues, E‐MC acts against contractile responses that preferentially recruit receptor‐operated Ca 2+ channels (ROCCs), a finding that clearly differs from other volatile compounds that preferentially act on electromechanically induced contractions . In strips from rat gastrointestinal smooth muscle, both EOOM and E‐MC exerted equipotent antispasmodic effects against KCl‐ and carbachol‐induced contractions, which likely resulted from a decrease in Ca 2+ levels in smooth muscle cells .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The dry roots of S. sibiricum yield an essential oil containing a-pinene and b-pinene, myrcene, limonene, p-cymene, b-phellandrene (major constituent), fenchone, fenchyl alcohol and acetate, fenchyl hydroxycinnamate, osthol, p-hydroxy cinnamate, sesibricin, imperatorin and bergapten. [27] According to the abovementioned literature data, more than 50% of SP1 tested oil was potentially vasorelaxant active. The action appears to be tranquillizing.…”
Section: Vasorelaxant Activitymentioning
confidence: 97%